SIRT2-PFKP interaction dysregulates phagocytosis in macrophages with acute ethanol-exposure - Gandhirajan, Anugraha; Roychowdhury, Sanjoy; Kibler, Christopher; Cross, Emily; Abraham, Susamma; Bellar, Annett; Nagy, Laura E.; Scheraga, Rachel Greenberg; Vachharajani, Vidula (Frontiers in Immunology, 2023)
Alcohol abuse, reported by 1/8th critically ill patients, is an independent risk factor for death in sepsis. Sepsis kills over 270,000 patients/year in the US. We reported that the ethanol-exposure suppresses innate-immune response, impairs pathogen clearance, and decreases survival in sepsis-mice via sirtuin 2 (SIRT2). SIRT2 is an NAD+-dependent histone-deacetylase with anti-inflammatory properties. We hypothesized that in ethanol-exposed macrophages, SIRT2 suppresses phagocytosis and pathogen clearance by regulating glycolysis. Immune cells use glycolysis to fuel increased metabolic and energy demand of phagocytosis. Using ethanol-exposed mouse bone marrow- and human blood monocyte-derived macrophages, we found that SIRT2 mutes glycolysis via deacetylating key glycolysis regulating enzyme phosphofructokinase-platelet isoform (PFKP), at mouse lysine 394 (mK394, human: hK395). Acetylation of PFKP at mK394 (hK395) is crucial for PFKP function as a glycolysis regulating enzyme. The PFKP also facilitates phosphorylation and activation of autophagy related protein 4B (Atg4B). Atg4B activates microtubule associated protein 1 light chain-3B (LC3). LC3 is a driver of a subset of phagocytosis, the LC3-associated phagocytosis (LAP), which is crucial for segregation and enhanced clearance of pathogens, in sepsis. We found that in ethanol-exposed cells, the SIRT2-PFKP interaction leads to decreased Atg4B-phosphorylation, decreased LC3 activation, repressed phagocytosis and LAP (Figure 1). Genetic deficiency or pharmacological inhibition of SIRT2 reverse PFKP-deacetylation, suppressed LC3-activation and phagocytosis including LAP, in ethanol-exposed macrophages to improve bacterial clearance and survival in ethanol with sepsis mice.